Work-From-Home Insights: Analyzing Employee Performance And Professional Relationship - Mirji, Hema; Vivekanantharasa, Raveenthiran (Sekolah Tinggi Manajemen IPMI, 2025)
Does work from home create better avenue for employers to work effectively and produce greater results? What are the potentials and pitfalls as far as employee’s relationship with organizations concerned? In recent research, there have been rising debates about exploring work from home as a strategy of boosting the efficiency of employees in public and private organizations. As a result of this, a body of literature created on this issue through examining various issues and embark scholars to debate on this issue. While some studies suggest work from home as an effective strategy, some others discard this on the ground of various challenges that the employees encountered because of this. However, the present research paper uses the phenomenology approach to seek the opinions from both the employees working from home and HR managers those who are associated with this system and seeks answers of these questions. The paper suggests that there is mixed experience among the employees and HR Managers about this system. It argues that though the leadership is observed technically oriented and micromanaging, employees are found satisfied over structured communication of team leaders. Further, there is a need to take up quantitative study to learn and establish the relationship between the involvement of the employees and effective leadership practices.